Matrix composition determines the dimensions of Bacillus subtilis NCIB 3610 biofilm colonies grown on LB agar. Issue 51 (21st June 2017) - Kesel, Sara; von Bronk, Benedikt; Falcón García, Carolina; Götz, Alexandra; Lieleg, Oliver; Opitz, Madeleine
Abstract : Exopolymeric substances secreted by biofilm forming Bacillus subtilis NCIB 3610 bacteria influence the growth and final dimensions of these biofilms. Abstract : The production of biomolecules can provide new functionalities to the synthesizing organism. One important example is the secretion of extracellular polymeric substances (EPS) by biofilm forming bacteria. This biofilm matrix protects the individual bacteria within the biofilm from external stressors such as antibiotics, chemicals and shear flow. Previous studies have determined several main matrix components of biofilms formed by Bacillus subtilis . However, how these matrix components influence the growth behavior and final dimensions of B. subtilis biofilms has not yet been determined. Here, we combine different experimental techniques with theoretical modeling to assess this relation. In particular, we quantify the area covered by the biofilm and the biofilm height by performing time-lapse microscopy and light profilometry, respectively. We study the development of biofilms formed by two wild-type strains (B-1 and NCIB 3610) differing in their matrix composition and NCIB 3610 mutant strains lacking the ability to produce specific EPS. Based on the experimentally obtained growth dynamics, we develop a mathematical model that allows us to quantify the influence of three key biofilm matrix components on the final NCIB 3610 biofilm colony dimensions. In detail, we show that two matrix components, the exopolysaccharide produced by the epsA-O operon and the surface layer protein BslA control the area covered by the biofilm colony. The height of these mature biofilm colonies is mostly affected by BslA. Together, our results emphasize the importance of the biofilm matrix composition for biofilm growth and the final dimensions of mature B. subtilis NCIB 3610 biofilm colonies.